THE INFLUENCE OF MARKETING MIX ON SALES VOLUME AT RIZQI STORE, TAWANGSARI VILLAGE, GARUM DISTRICT, BLITAR REGENCY - Tsania Rahmawati; Hanik Amaria (Universitas Islam Balitar, 2023)
More and more needs make people’s demand and purchasing power also increase. Therefore, the title of this research is The Effect of Marketing Mix Strategy on Increasing Sales Volume at Rizqi Store, Tawangsari Village, Garum District, Blitar Regency. The research method used is the quantitative research method. The population used is all consumers who buy at Rizqi Store, Tawangsari Village, Garum District, Blitar Regency with a sample size of 80 respondents and sampling techniques using simple random sampling. The data collection technique used a questionnaire and data analysis was assisted by the SPSS Statistics 26 application. Based on the results of this study, product, and promotion have a positive and significant effect on increasing sales volume, while price and place have no effect and are insignificant to increasing sales volume at Rizqi Store, Tawangsari Village, Garum District, Blitar Regency. Simultaneously or together, product, price, place, and promotion affect increasing sales volume at Rizqi Store, Tawangsari Village, Garum District, Blitar Regency.